Re-imagining environmental governance (2020)
This article describes and analyses an encounter in the Colombian Amazon between Indigenous practices and arrangements to manage their environment and the conservation policies of the State. Indigenous peoples understand their world as populated by powerful human and nonhuman beings; for them, the moral duty of achieving happiness and abundance for all implies sustaining reciprocal and respectful relations with these beings (including the State). In contrast Colombian environmental policy distinguishes between nature and culture, seeking to safeguard landscapes from human interference so that natural processes can unfold unhindered. In practice these partially connected, yet incommensurable worldviews make for a ‘perfect storm’ - opening opportunities for illegal mining. Drawing on recent fieldwork among the Andoke, an ethnic group well acquainted with extractivism in its different historical modalities and presently affronting the fallout of gold dredge mining we narrate how a parallel, non-state governance system makes it difficult for them to care for their land and entertain mutual and respectful relations with human and nonhuman beings (which we translate as ‘territorial health’). We conclude by arguing for the need to re-imagine environmental governance in ways that more closely engage with what we call pluriversal governance: a form of (environmental) governance that does ontological justice to those involved in the environmental conflict – including, crucially, Indigenous people.